Benzimidazole functionalized covalent triazine frameworks for CO2 capture. Issue 30 (12th July 2016) - Tao, Liming; Niu, Fang; Wang, Chao; Liu, Jingang; Wang, Tingmei; Wang, Qihua
Abstract : Benzimidazole functionalized covalent triazine frameworks exhibited high BET surface areas up to 1500 m 2 g −1, high CO2 adsorption capacities up to 21.7 wt% at 273 K, and high CO2 /N2 selectivities up to 102.7 at a high temperature of 303 K. Abstract : A series of covalent triazine frameworks containing benzimidazole segments (CTF-BIs) were designed and prepared by dynamic trimerization under ionothermal conditions, based on the novel designed dicyano monomer of dicyano benzimidazole (DCBI). The CTF-BIs were all amorphous and exhibited BET surface areas up to 1549 m 2 g −1 . The effect of reaction conditions including the ratio of catalyst and temperature on the pore properties was discussed. Meanwhile, the CO2 adsorption capacity of all the CTF-BIs was studied and it was found that the CO2 uptake capacity was as high as 21.68 wt% at 273 K and 1.10 bar for CTF-BI-11. The CTF-BIs exhibited high selectivities for CO2 over N2 in the range of 31.3–88.5 at 273 K, and 29.0–102.7 at 303 K, respectively.